Structural and Functional Determinants of Rodent and Human Surfactant Protein A: A Synthesis of Binding and Computational Data - Nalian, Armen; Umstead, Todd M.; Yang, Ching-Hui; Silveyra, Patricia; Thomas, Neal J.; Floros, Joanna; McCormack, Francis X.; Chroneos, Zissis C. (Frontiers in Immunology, 2019)
Surfactant protein A (SP-A) provides surfactant stability, first line host defense, and lung homeostasis by binding surfactant phospholipids, pathogens, alveolar macrophages (AMs), and epithelial cells. Non-primates express one SP-A protein whereas humans express two: SP-A1 and SP-A2 with core intra- and inter-species differences in the collagen-like domain. Here, we used macrophages and solid phase binding assays to discern structural correlates of rat (r) and human (h) SP-A function. Binding assays using recombinant rSP-A expressed in insect cells showed that lack of proline hydroxylation, truncations of amino-terminal oligomerization domains, and site-directed serine (S) or alanine (A) mutagenesis of cysteine 6 (C6S), glutamate 195 (E195A), and glutamate 171 (E171A) in the carbohydrate recognition domain (CRD) all impaired SP-A binding. Replacement of arginine 197 with alanine found in hSP-A (R197A), however, restored the binding of hydroxyproline-deficient rSP-A to the SP-A receptor SP-R210 similar to native rat and human SP-A. In silico calculation of Ca++ coordination bond length and solvent accessibility surface area revealed that the “humanized” R197A substitution alters topology and solvent accessibility of the Ca++ coordination residues of the CRD domain. Binding assays in mouse AMs that were exposed to either endogenous SP-A or hSP-A1 (6A2) and hSP-A2 (1A0) isoforms in vivo revealed that mouse SP-A is a functional hybrid of hSP-A1 and hSP-A2 in regulating SP-A receptor occupancy and binding affinity. Binding assays using neonatal and adult human AMs indicates that the interaction of SP-A1 and SP-A2 with AMs is developmentally regulated. Furthermore, our data indicate that the auxiliary ion coordination loop encompassing the conserved E171 residue may comprise a conserved site of interaction with macrophages, and SP-R210 specifically, that merits further investigation to discern conserved and divergent SP-A functions between species. In summary, our findings support the notion that complex structural adaptation of SP-A regulate conserved and species specific AM functions in vertebrates.